Analisis kadar Monosodium Glutamat (MSG) pada berbagai macam jenis kuah soto menggunakan refraktometer abbe - Ariska, Lambang Putri Ayu (Maliki Interdisciplinary Journal, 2024)
Monosodium glutamate (MSG) is the sodium salt of glutamic acid (a non-essential amino acid). Monosodium glutamate is widely used as a food flavoring. This study aims to determine the levels of monosodium glutamate in homemade soto sauce and instant products circulating around UIN Maulana Malik Ibrahim Malang. Based on the results of the research that has been done, the monosodium glutamate content of the 5 samples is 2%, 3%, 4%, and 5% where the lowest MSG content is found in the “sedap soto” noodle soup sample with 5% content and the highest level in the soup sample. soto “super porridge” with 2% content by weight of MSG from 5 samples is 0.3 gr, 0.4 gr, 0.2 gr, 0.2-0.3 gr and 0.5 gr. Therefore soto sauce can be consumed 1 serving per day judging from the weight of MSG which is still between the set threshold of 0.3-1 gram per day.